Clinical management of parasitic gastroenteritis (PGE) concurrent with moderate pneumonia in a goat: a clinical veterinary case report - Jesse, Faez Firdaus Abdullah; Hambali, Idris Umar; Galli, Mohamad Fauzi Bin Taslim; Abba, Yusuf; Bitrus, Asinamai Athliamai; Pete, Innocent Damudu; Lila, Mohd Azmi Mohd; Haron, Abd Wahid; Muhamad, Azim Salahuddin (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Gastro-enteritis is a parasitic disease caused by the nematode species which is considered as an important parasite in Malaysia. This case report described the management of Parasitic Gastro-enteritis concurrent with pneumonia in goat. Materials and methods: The Jamnapari cross goat aged two years and weighing 40 Kg was presented to the Universiti Veterinary Hospital, Universiti Putra Malaysia with the history of diarrhea and depression. The goat was examined physically. Blood and fecal samples were collected for complete blood count, serum biochemistry analysis and parasitological examination. Standard treatment plan was applied for the correction of the the problem. Results: Physical examination findings revealed the goat was in poor body condition, dull and depressed. Wet and dry fecal traces were observed around the groin region. The temperature was slightly elevated (39.5°C), the heart rate was increased (160 b/min) while other parameters were within normal range. Upon auscultation of the thoracic region, moderate crackle lung sound was determined. Visual observation of the nasal cavity indicated a bilateral mucopurulent nasal discharge. The hemogram result revealed evidence of a normocytic normochromic anemia, leukocytosis, neutrophilia with left shift and monocytosis. Serum biochemistry revealed increases in gamma-glutamyl transferase (GGT), sodium, chloride, creatine kinase (CK), and hyperglobulinemia. Fecal examination revealed increased in Strongyle egg count of about 2,700 eggs per gram of feces using the Modified Mcmaster technique. From the history, physical examination and laboratory findings the goat was diagnosed with clinical parasitic gastroenteritis (PGE) concurrent with moderate pneumonia infection. The therapeutic plan for this case were 45 mL of kaolin-pectin (30 mL/Kg body weight) orally SID for 3 days as anti-diarrhea, 12 mL Levamisole (12 mg/Kg bwt) was administered orally once as anthelminthic, fluid therapy was instituted using 1.5 L of Lactated Ringers solution once via intravenously. Trimethoprim-Sulfamethoxazole (1 mL/16 Kg bwt) was administered intramuscularly SID for 3 days. Conclusion: Follow up examination of the goat a week post treatment indicated a good prognosis as the nasal discharges were cleared, diarrhea stopped and the goat was active. http://doi.org/10.5455/javar.2017.d219